Acute physical exercise under hypoxia improves sleep, mood and reaction time - de Aquino-Lemos, V.; Vagner T. Santos, R.; Moreira Antunes, H. K.; Lira, F. S.; Luz Bittar, I. G.; Caris, A. V.; Tufik, S.; de Mello, M. T. (Physiology & Behavior, 2016)
This study aimed to assess the effect of two sessions of acute physical exercise at 50% VO2peak performed under hypoxia (equivalent to an altitude of 4500 m for 28 h) on sleep, mood and reaction time. Forty healthy men were randomized into 4 groups: Normoxia (NG) (n = 10); Hypoxia (HG) (n = 10); Exercise under Normoxia (ENG) (n = 10); and Exercise under Hypoxia (EHG) (n = 10). All mood and reaction time assessments were performed 40 min after awakening. Sleep was reassessed on the first day at 14 h after the initiation of hypoxia; mood and reaction time were measured 28 h later. Two sessions of acute physical exercise at 50% VO2peak were performed for 60 min on the first and second days after 3 and 27 h, respectively, after starting to hypoxia. Improved sleep efficiency, stage N3 and REM sleep and reduced wake after sleep onset were observed under hypoxia after acute physical exercise. Tension, anger, depressed mood, vigor and reaction time scores improved after exercise under hypoxia. We conclude that hypoxia impairs sleep, reaction time and mood. Acute physical exercise at 50% VO2peak under hypoxia improves sleep efficiency, reversing the aspects that had been adversely affected under hypoxia, possibly contributing to improved mood and reaction time.